Creation of an Applicability Matrix of Modeling Methods Depending on the Complexity of Pore Space for Carbonate Fractured Reservoirs; Saint Petersburg 2018: Innovations in Geosciences - Time for Breakthrough - Korigov R. M. Ramazan Musaevich (Building Models of Reservoir Processes and Systems, 2018)
Title screen